Evidence for continuing current in sprite-producing cloud-to-ground lightning - Reising, Steven C., author; Bell, Timothy F., author; Inan, Umran S., author; Lyons, Walter A., author; American Geophysical Union, publisher (Colorado State University. Libraries, 1996)
Radio atmospherics launched by sprite producing positive cloud-to-ground lightning flashes and observed at Palmer Station, Antarctica, exhibit large ELF slow tails following the initial VLF portion, indicating the presence of continuing currents in the source lightning flashes. One-to-one correlation of sferics with NLDN lightning data in both time and arrival azimuth, measured with an accuracy of ±1° at ~12,000 km range, allows unambiguous identification of lightning flashes originating in the storm of interest. Slow-tail measurements at Palmer can potentially be used to measure continuing currents in lightning flashes over nearly half of the Earth's surface.